PENGARUH MODAL KERJA TERHADAP RENTABILITAS PADA PT. PERKEBUNAN NUSANTARA IV MEDAN - Dearma Sariani Sinaga (JURNAL GLOBAL MANAJEMEN, 2020)
Working capital is what compares current assets after deducting current liabilities and Profitability is the abilitiy of a company to show a comparison between profit and capital flow assets generated by this profit. Data analysis used in descriptive, Normality Test, and simple linear regression. While testing the hypothesis that is done is the t test and the coefficient of determination. The results of this study indicate that working capital affects profitability. The results of the t-test analysis resulted in a t-count 3,916 > t-tabel 1860 with a sifnificance level of 0,004 < 0,05, with a simple linear regression alaysis obtained Y= -1,289+0,059 where the increase in working capital was 1% then the profitability also increased by 0,059 %. From meaning that the percentage of working capital to profitability is 65,7 % while the remaining 34,3 % is explained by other variabels not included in the research variabel.